Optimization of an oral mucosa in vitro model based on cell line TR146. Issue 2 (2nd April 2020) - Lin, Grace C.; Leitgeb, Tamara; Vladetic, Alexandra; Friedl, Heinz-Peter; Rhodes, Nadine; Rossi, Angela; Roblegg, Eva; Neuhaus, Winfried
ABSTRACT: During the last years, the popularity of saliva has been increasing for its applicability as a diagnostic fluid. Blood biomarker molecules have to cross the blood-saliva barrier (BSB) in order to appear in saliva. The BSB consists of all oral and salivary gland epithelial barriers. Within this context, the optimization of in vitro models for mechanistic studies about the transport of molecules across the oral mucosa is an important task. Here, we describe the optimization and comprehensive characterization of a Transwell model of the oral mucosa based on the epithelial cell line TR146. Through systematic media optimization investigating 12 different set-ups, a significant increase of barrier integrity upon airlift cultivation was achieved for TR146 cell layers. The distinct improvement of the paracellular barrier was shown by measurements of transepithelial electrical resistance (TEER) and carboxyfluorescein permeability assays. Histological characterization supported TEER data and showed a stratified, non-keratinized multilayer of the optimized TR146 model. High-Throughput qPCR using 96 selected markers for keratinization, cornification, epithelial–mesenchymal transition, aquaporins, mucins, tight junctions, receptors, and transporter proteins was applied to comprehensively characterize the systematic optimization of the cellular model and validate against human biopsy samples. Data revealed the expression of several genes in the oral mucosa epithelium for the first time and elucidated novel regulations dependent on culture conditions. Moreover, functional activity of ABC transporters ABCB1 and ABCC4 was shown indicating the applicability of the model for drug transport studies. In conclusion, a Transwell model of the oral mucosa epithelium was optimized being suitable for transport studies.